Epidural Dexamethasone for Postoperative Analgesia in Patients Undergoing Unilateral Inguinal Herniorrhaphy: A Comparative Study - M. R. Razavizadeh; MR. Fazel; N. Heydarian; F. Atoof (Pain Research and Management)
Background. This study was designed to evaluate the effect of adding dexamethasone to epidural bupivacaine on postoperative analgesia in unilateral inguinal herniorrhaphy. Methods. Forty-four patients were enrolled in this double-blind, clinical trial study. Patients were randomly allocated into dexamethasone or control group. In the dexamethasone group, patients received 18 ml of bupivacaine 0.5% and 2 ml (8 mg) of dexamethasone; in the control group, patients received 18 ml of bupivacaine 0.5% and 2 ml of normal saline. The onset of sensory block and its duration and incidence of nausea and vomiting were recorded. Results. The onset of epidural anesthesia was significantly more rapid in the dexamethasone group than in the control group (P<0.001). Duration of analgesia was markedly prolonged in the dexamethasone group than in the control group (P<0.001). Five patients (22.7%) in the control group had nausea in the first hour after the procedure (P=0.048). None of the patients in the dexamethasone group had nausea. None of our patients had vomiting in the two groups. Conclusions. This study showed that adding dexamethasone to bupivacaine significantly prolongs the duration of postoperative analgesia. This trial is registered with Iranian Registry of Clinical Trials (IRCT) number IRCT2012062910137N1.